Sex-Specific Associations Between Low Muscle Mass and Glucose Fluctuations in Patients With Type 2 Diabetes Mellitus - Shi, Xiulin; Liu, Wenjuan; Zhang, Lulu; Xiao, Fangsen; Huang, Peiying; Yan, Bing; Zhang, Yiping; Su, Weijuan; Jiang, Qiuhui; Lin, Mingzhu; Liu, Wei; Li, Xuejun (Frontiers in Endocrinology, 2022)
ABSTRACT Objective: Studies have shown that sex differences in lean mass, concentrations of sex hormones, and lifestyles have an influence on muscle health and glucose metabolism. We investigated the sex-specific association between low muscle mass and glucose fluctuations in hospitalized patients with type 2 diabetes mellitus (T2DM) receiving continuous subcutaneous insulin infusion (CSII) therapy. Methods: A total of 1084 participants were included. Body composition was determined by dual-energy X-ray absorptiometry. Largest amplitude of glycemic excursions (LAGE) and standard deviation of blood glucose (SDBG) were calculated to estimate intraday blood glucose fluctuations. Results: The prevalence of low muscle mass was higher in males than in females (p<0.001). There was a significant sex-specific interaction between the status of low muscle mass and glucose fluctuations (LAGE and SDBG) (p for interaction=0.025 and 0.036 for SDBG and LAGE, respectively). Among males, low muscle mass was significantly associated with a higher LAGE and SDBG (difference in LAGE: 2.26 [95% CI: 1.01 to 3.51], p < 0.001; difference in SDBG: 0.45 [95% CI: 0.25 to 0.65], p < 0.001) after adjustment for HbA1c, diabetes duration, hyperlipidemia, diabetic peripheral neuropathy, diabetic nephropathy, and cardiovascular disease. These associations remained significant after further adjustment for age and C-peptide. Among females, low muscle mass was not associated with LAGE or SDBG after adjustment for all covariates. Conclusion: The prevalence of low muscle mass was higher in males than in females. Low muscle mass was significantly associated with higher LAGE and SDBG among males, but not females.